2014
DOI: 10.4236/jcpt.2014.41007
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Liquid Crystal Thermography in Selected Technical and Medical Applications—Recent Development

Abstract: Thermochromic liquid crystals (TLC) and true-colour digital image processing have been successfully used in non-intrusive technical, industrial and biomedical studies and applications. Thin coatings of TLC at surfaces are utilized to obtain detailed temperature distributions and heat transfer rates for steady or transient processes. Liquid crystals also can be used to make the temperature and velocity fields in liquids visible by the simple expedient of directly mixing the liquid crystal material into the liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…Eventually the liquid crystal phase appears opaque as the resulting increase in pitch reflects light outside the visible wavelength range. Such materials have been used in thermal mapping and analysis in medical, industrial, and engineering applications such as dynamic heat transfer measurements [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Eventually the liquid crystal phase appears opaque as the resulting increase in pitch reflects light outside the visible wavelength range. Such materials have been used in thermal mapping and analysis in medical, industrial, and engineering applications such as dynamic heat transfer measurements [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Stasiek et al [6] have shown the use of TLCs in biomedicine, where we can meet with measurements that can non-invasively detect cancer. The TLC layer is applied to the skin surface and the temperature field in this area is monitored.…”
Section: Introductionmentioning
confidence: 99%
“…The macroscopic chirality of liquid crystalline phase results in special properties such as selective reflection of light and/or (anti)ferroelectricity , which are extremely useful in many applications, e.g. thermographic devices for diagnostics , ultrafast and energy‐saving displays, and sensors . Newly, the effect of chiral ionic liquids as mobile phase (MP) additives on the chiral recognition of acidic enantiomers on a teicoplanin‐based chiral stationary phase has been demonstrated .…”
Section: Introductionmentioning
confidence: 99%